TINJAUAN FIKIH SIYASAH TERHADAP PEMILIHAN RT/RW DI KELURAHAN BUAKANA KOTA MAKASSAR - Marwah, Dhirga Tri Setiawan R; Syamsuddin, Darussalam; Maloko, M. Thahir (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
The purpose of this study is to describe (1) to determine the implementation of democracy in the election of RT/RW according to the laws and regulations in Indonesia (2) To find out fiqh siyasah on the implementation of RT/RW elections. In answering these problems, the author uses a syar'i normative approach and an empirical juridical approach. The method of data collection is done by means of interviews, observation, documentation, and literature study. The results of this discussion and research are (1) The implementation of democracy in Buakana village still needs to be improved, because the implementation of the regulations is still not running according to the applicable law and there are still many people who have not played an active role in the context of the democratic party in Buakana village. and there are still many things that need to be improved both in terms of ethical procedures, transparency, both in the election committee, on the part of the community so that it does not happen again. 2) Islam itself has decided that in making decisions for the benefit of the people, it should be done by deliberation and consensus, so that the decision can be accepted by all groups of society.